2015
DOI: 10.1371/journal.pone.0141236
|View full text |Cite
|
Sign up to set email alerts
|

A European Concern? Genetic Structure and Expansion of Golden Jackals (Canis aureus) in Europe and the Caucasus

Abstract: In the first continent-wide study of the golden jackal (Canis aureus), we characterised its population genetic structure and attempted to identify the origin of European populations. This provided a unique insight into genetic characteristics of a native carnivore population with rapid large-scale expansion. We analysed 15 microsatellite markers and a 406 base-pair fragment of the mitochondrial control region. Bayesian-based and principal components methods were applied to evaluate whether the geographical gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 116 publications
7
75
0
2
Order By: Relevance
“…Although the recent expansion of the golden jackal in the Baltic countries has generated concerns about its possible negative effects on other wildlife species and livestock via predation or transmission of pathogens, and has led to it being labelled as a potentially invasive alien species, the prevailing opinion in other countries does not support this attitude (Banea et al 2015; Rutkowski et al 2015; Science for Environment Policy 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recent expansion of the golden jackal in the Baltic countries has generated concerns about its possible negative effects on other wildlife species and livestock via predation or transmission of pathogens, and has led to it being labelled as a potentially invasive alien species, the prevailing opinion in other countries does not support this attitude (Banea et al 2015; Rutkowski et al 2015; Science for Environment Policy 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, it should be remembered that the observed range expansion is essentially favoured by a pronounced capability of the species for a long-distance leptokurtic disperal. Rutkowski et al (2015) report a number of records of long-distance movements and demonstrate a dual origin of the population in Baltic region recently established first by immigrants of the Caucasian haplotype followed by those of the south-eastern European origin.…”
Section: Introductionmentioning
confidence: 97%
“…Trontelj and Utevsky (2012) then noted the need for an analysis using microsatellites exhibiting high levels of polymorphism. The use of nuclear microsatellites (nSSR) in combination with mitochondrial DNA (mtDNA) sequences for studies on leech species provides an opportunity to track the phylogeographical history, as previously reported for other animal species (e.g., Konishi, Hata, Matsuda, Arai, & Mizoguchi, 2017;López-Uribe, Cane, Minckley, & Danforth, 2016;Michaelides et al, 2015;Rutkowski et al, 2015;Shoda-Kagaya et al, 2010). However, few genetic analyses on leech species using nSSR markers have been conducted (e.g., Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This range has, however, expanded westward and northward since the mid-twentieth century (Arnold et al, 2012), and immigrant individuals have recently been observed, or caught in Switzerland, Austria and other countries surrounding the Baltic Sea (e.g. Kowalczyk et al, 2015;Rutkowski et al, 2015;Trouwborst et al, 2015). Bulgaria currently has the largest population of the golden jackal among European countries (Arnold et al, 2012).…”
Section: Introductionmentioning
confidence: 99%